THE EFFECTS OF SALES GROWTH, PROFITABILITY, LIQUIDITY, LEVERAGE AGAINST FINANCIAL DISTRESS - Edison, Acep; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted based on the financial difficulties of retail companies listed on the Indonesia Stock Exchange. The research is intended to prove the allegation that financial distress that occurs in companies is influenced by sales growth, profitability, liquidity, and leverage. This type of research is explanatory, and the population of the study is 25. The number of samples of 6 companies was taken using the purposive sampling technique with criteria for retail companies to experience a decline in operating profit for two consecutive years in the 2014-2018 period. The data is processed using eviews 10.0 data processing program and the results of the research prove that Sales growth and Liquidity cannot be analyzed because it do not meet the significance test and are not meaningful, Profitability has a negative effect on financial distress, and Leverage has a positive effect on Financial Distress